Prognostic value of human leukocyte antigen G expression in solid tumors: a systematic review and meta-analysis - Bartolome, Jorge; Molto, Consolacion; Benitez-Fuentes, Javier David; Fernandez-Hinojal, Gonzalo; Manzano, Aranzazu; Perez-Segura, Pedro; Mittal, Abhenil; Tamimi, Faris; Amir, Eitan; Ocana, Alberto (Frontiers in Immunology, 2023)
Identification of modulators of the immune response with inhibitory properties that could be susceptible for therapeutic intervention is a key goal in cancer research. An example is the human leukocyte antigen G (HLA-G), a nonclassical major histocompatibility complex (MHC) class I molecule, involved in cancer progression. In this article we performed a systematic review and meta-analysis on the association between HLA-G expression and outcome in solid tumors. A total of 25 studies met the inclusion criteria. These studies comprised data from 4871 patients reporting overall survival (OS), and 961 patients, reporting disease free survival (DFS). This study was performed in accordance with PRISMA guidelines and registered in PROSPERO. HLA-G expression was associated with worse OS (HR 2.09, 95% CI = 1.67 to 2.63; P < .001), that was higher in gastric (HR = 3.40; 95% CI = 1.64 to 7.03), pancreatic (HR = 1.72; 95% CI = 0.79 to 3.74) and colorectal (HR = 1.55; 95% CI = 1.16 to 2.07) cancer. No significant differences were observed between the most commonly utilized antibody (4H84) and other methods of detection. HLA-G expression was associated with DFS which approached but did not meet statistical significance. In summary, we describe the first meta-analysis associating HLA-G expression and worse survival in a variety of solid tumors.